Effects of saffron (Crocus sativus L.) supplementation on inflammatory biomarkers: A systematic review and meta‐analysis. (11th June 2020) - Asbaghi, Omid; Sadeghian, Mehdi; Sadeghi, Omid; Rigi, Somaye; Tan, Shing Cheng; Shokri, Azad; Mousavi, Seyed Mohammad
Abstract : The effect of saffron supplementation on subclinical inflammation remains inconclusive. We performed a systematic review and meta‐analysis to summarize available findings on the effect of saffron supplementation on inflammatory biomarkers (C‐reactive protein [CRP], tumor necrosis factor‐α [TNF‐α], and interleukin‐6 [IL‐6]) in adults. We searched PubMed/Medline, Scopus, Web of Science, and Google Scholar databases up to November 2019 using relevant keywords to identify eligible trials. All randomized controlled trials (RCTs) that examined the effect of oral saffron supplementation on plasma concentrations of CRP, TNF‐α, and IL‐6 were included. For each outcome, mean differences and SD s were pooled using a random‐effects model. Overall, eight RCTs were included in this meta‐analysis. The pooled results showed that saffron supplementation did not result in significant changes in serum CRP (weighted mean difference [WMD]: −0.43 mg/L; 95% confidence interval [CI]: −1.04 to 0.17; p = .16), serum TNF‐α (WMD: −1.29 pg/mL; 95% CI: −4.13 to 1.55; p = .37), and IL‐6 concentrations (WMD: 0.11 pg/mL; 95% CI: −0.79 to 1.00; p = .81). Subgroup analysis indicated a significant reduction in serum CRP levels in studies with baseline CRP of ≥3 mg/L, saffron dosage of ≤30 mg/day, and intervention duration of <12 weeks, as well as trials that used crocin. Similarly, saffron was found to decrease TNF‐α in studies that recruited non‐diabetic subjects, subjects with baseline levels of ≥15 pg/mL, and participants with <50 years old, as well as trials that administered saffron at the dosage of ≤30 mg/day. We also found a significant non‐linear effect of saffron dosage on serum CRP concentrations ( p non‐linearity = .03). The overall results indicated that saffron supplementation did not affect inflammatory cytokines. Further high‐quality studies are needed to firmly establish the clinical efficacy of supplemental saffron on inflammatory biomarkers.